Large-conductance Ca2+-activated potassium channels are potently involved in the inverse neurovascular response to spreading depolarization - Ákos Menyhárt; Attila E. Farkas; Dániel P. Varga; Rita Frank; Réka Tóth; Armand R. Bálint; Péter Makra; Jens P. Dreier; Ferenc Bari; István A. Krizbai; Eszter Farkas (Neurobiology of Disease, 2018)
Recurrent spreading depolarizations occur in the cerebral cortex from minutes up to weeks following acute brain injury. Clinical evidence suggests that the immediate reduction of cerebral blood flow in response to spreading depolarization importantly contributes to lesion progression as the wave propagates over vulnerable tissue zones, characterized by potassium concentration already elevated prior to the passage of spreading depolarization. Here we demonstrate with two-photon microscopy in anesthetized mice that initial vasoconstriction in response to SD triggered experimentally with 1 M KCl is coincident in space and time with the large extracellular accumulation of potassium, as shown with a potassium indicator fluorescent dye. Moreover, pharmacological manipulations in combination with the use of potassium-sensitive microelectrodes suggest that large-conductance Ca2+-activated potassium (BK) channels and L-type voltage-gated calcium channels play significant roles in the marked initial vasoconstriction under elevated baseline potassium. We propose that potassium efflux through BK channels is a central component in the devastating neurovascular effects of spreading depolarizations in tissue at risk.